KEPEMIMPINAN HINDU (Dalam Nitisastra dan Susastra Hindu Ramayana) - I Made Suweta (PARIKSA: Jurnal Hukum Agama Hindu, 2019)
Leadership in Hinduism is found in Nitisastra. Nitisastra comes from the words niti and sastra. The word niti means worldly wisdom, social political ethics, guidance and also means knowledge of the state or the science of political building based on the teachings of Hindu religions. Based on the etymological understanding above, the definition of nitisastra can be expanded further, namely the aim of science, to build a country both in terms of its governance, governance, and social order. In developing the country, the government and the people of nitisastra put the moral values of Hinduism as the foundation. In this sense nitisastra is not the science of government of a particular Hindu country, because nitisastra is applicable not only in general and theoretically, but also contains practical values. Based on a glimpse of the background above, there are several issues that will be discussed which can be formulated as follows: (1) how is leadership in nitisastra ?, (2) how is the leadership of Rama and Laksmana in the Hindu Ramayana ?, and (3) how is the relationship between Rama's leadership and Laksmana with Nitisastra? While the purpose of discussing this problem are: (1) to know the leadership in nitisastra, (2) to find out the leadership of Rama and Laksmana in the Hindu Ramayana literature, and (3) to find out the relation between Rama and Laksmana's leadership with nitisastra. The results of the discussion in this study are: (1) Leadership in Hinduism is found in nitisastra, (2) In developing the country, the nitisastra government and society put the moral values of Hinduism as its foundation, (3) Hindu leadership in the Ramayana is closely related to teaching Asta Brata's leadership in which there are spiritual values namely truth, honesty, simplicity, caring, cooperation, freedom, peace, love, understanding, good deeds, giving, responsibility, feeling, integrity, hygiene, humility heart, loyalty, precision, courage, glory, gratitude, perseverance, patience, justice, sincerity and determination.